Identification and localization of minimal MHC-restricted CD8+ T cell epitopes within the Plasmodium falciparum AMA1 protein - Sedegah, Martha (BioMed Central, 2010)
BACKGROUND: Plasmodium falciparum apical membrane antigen-1 (AMA1) is a leading malaria vaccine candidate antigen that is expressed by sporozoite, liver and blood stage parasites. Since CD8+ T cell responses have been implicated in protection against pre-erythrocytic stage malaria, this study was designed to identify MHC class I-restricted epitopes within AMA1. METHODS: A recombinant adenovirus serotype 5 vector expressing P. falciparum AMA1 was highly immunogenic when administered to healthy, malaria-naive adult volunteers as determined by IFN-γ ELISpot responses to peptide pools containing overlapping 15-mer peptides spanning full-length AMA1. Computerized algorithms (NetMHC software) were used to predict minimal MHC-restricted 8-10-mer epitope sequences within AMA1 15-mer peptides active in ELISpot. A subset of epitopes was synthesized and tested for induction of CD8+ T cell IFN-γ responses by ELISpot depletion and ICS assays. A 3-dimensional model combining Domains I + II of P. falciparum AMA1 and Domain III of P. vivax AMA1 was used to map these epitopes. RESULTS: Fourteen 8-10-mer epitopes were predicted to bind to HLA supertypes A01 (3 epitopes), A02 (4 epitopes), B08 (2 epitopes) and B44 (5 epitopes). Nine of the 14 predicted epitopes were recognized in ELISpot or ELISpot and ICS assays by one or more volunteers. Depletion of T cell subsets confirmed that these epitopes were CD8+ T cell-dependent. A mixture of the 14 minimal epitopes was capable of recalling CD8+ T cell IFN-γ responses from PBMC of immunized volunteers. Thirteen of the 14 predicted epitopes were polymorphic and the majority localized to the more conserved front surface of the AMA1 model structure. CONCLUSIONS: This study predicted 14 and confirmed nine MHC class I-restricted CD8+ T cell epitopes on AMA1 recognized in the context of seven HLA alleles. These HLA alleles belong to four HLA supertypes that have a phenotypic frequency between 23% - 100% in different human populations.